To use Hess's Law, we need to manipulate the given equations so that they can be combined to form the target equation: C2H5OH l 2CO2 g + 3H2 g .First, we need to reverse equation 1 and multiply it by 3/2 to get 3H2 g as a product:1' 3H2O l 3H2 g + 3/2 O2 g H = +3/2 * 484 kJ/mol = +726 kJ/molNext, we need to reverse equation 3 to get C2H5OH l as a reactant:3' C2H4 g + H2O g C2H5OH l H = -44 kJ/molNow, we can add equations 1', 2, and 3' to get the target equation:1' 3H2O l 3H2 g + 3/2 O2 g H = +726 kJ/mol2 C2H5OH l + 3O2 g 2CO2 g + 3H2O l H = -1,367 kJ/mol3' C2H4 g + H2O g C2H5OH l H = -44 kJ/mol-------------------------------------------------------------Target: C2H5OH l 2CO2 g + 3H2 g H = ?Now, we can sum the enthalpy changes:H = +726 kJ/mol - 1,367 kJ/mol - 44 kJ/mol = -685 kJ/molSo, the enthalpy change for the target reaction, C2H5OH l 2CO2 g + 3H2 g , is H = -685 kJ/mol.